Analisis Penyebaran Informasi Vaksin Covid-19 Pada Twitter Menggunakan Kolaborasi SNA dan Sentiment Analysis - Stanny Dewanty Rehatta; Eko Sediyono; Irwan Sembiring (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
The use of the Covid-19 vaccine as an effort to overcome and protect the Indonesian people from the Covid-19 pandemic has been widely discussed on Twitter social media. The existence of the Covid-19 vaccine in Indonesia has drawn various opinions because of the large amount of information shared by Twitter users regarding the Covid-19 vaccine. This study uses the collaboration of social network (SNA) and sentiment analysis. In this study, SNA collaborated with sentiment analysis to classify positive and negative sentiments in news spread by influential actors based on groups formed in the SNA network. SNA research shows there are 6 influential actors based on the group formed in the network. The actors with the highest popularity are @KemenkesRI with a degree of centrality reaching 194, while actors with the lowest degree of centrality are @rudeski83. In addition, actors with the highest centrality betweenness are @KemenkesRI because it plays an important role in disseminating information about the Covid-19 vaccine on social media twitter. SVM classification test results showed @KemenkesRI actor with an accuracy rate of 97% and @Vaksin_Update with an accuracy rate of 90% are actors with a positive sentiment percentage of 95%, while actors @rudeski83with an accuracy rate of 98% is an actor with a negative sentiment percentage of 80%. Based on the above, it can be seen that the SNA collaboration and sentiment analysis carried out showed that 5 out of 6 actors who were influential actors based on the group formed in the network.